Efficacy of Tooth Whitening Using Natural Products in Vitro - Randa Abidia; Ahmed A. El-Hejazi; Ambreen Azam; Shahad Al-Qhatani; Khuloud Al-Mugbel; Maryam AlSulami (Saudi Dental Journal)
Introduction: In recent years, a large number of patients are looking for whiter teeth by trying different tooth-whitening techniques. They tend to use natural homemade recipes such as; strawberries, coconut oil rinse, basil, lemon, activated charcoal, apple cider vinegar, baking soda, and turmeric. There is lack of studies done on these natural whitening products. Aim: To evaluate the efficacy of different homemade teeth whitening recipes in vitro. Materials and methods: A total of 30 caries free extracted anterior and premolars teeth were collected. They were cleaned and the roots were sectioned. Then, the teeth were mounted in epoxy resin (Buccal surface) and stored in 0.2% thymol solution. The teeth were divided into six groups; baking soda, activated charcoal, turmeric, strawberries, Colgate Optic Whitening toothpaste, and Opalescence 20% home bleaching system. Two machines were used in this study: Spectrophotometer (LabScan XE) and Toothbrush stimulator (Omron SD Mechatronik). Enamel shade for each sample was taken by spectrophotometer three times respectively for each sample. Baseline measurement for (ΔE, L*, a*, b*), the second reading was done after 5 days and the third reading was taken at the 10th day. For statistical inference, One-way repeated measurements were used followed by one-way ANOVA. Results: ΔE showed a significant difference in all groups except the turmeric group. Conclusion: Statistical difference was found among groups; baking soda, activated charcoal, strawberries, Colgate Optic Whitening toothpaste and Opalescence. Further studies are needed to measure the effect on the surface roughness and color stability.